THICKNESS ASSESSMENT OF SKIN LESION USING 3D SKIN SURFACE IMAGING - HURRIYATUL FITRIYAH, HURRIYATUL FITRIYAH (2012)
Thickness is one of the parameter to be assessed to determine the severity level and treatment efficacy of skin lesion. In practice, the dermatologists subjectively assess the skin lesion thickness using the tactile inspection which does not outcome a quantitative measure thus result inter-rater and intra-rater variation. The challenge in measuring thickness of skin lesions is that the surface curvature of human skin is undulate in 3D and varying at different body location. Several researches to objectively measure the skin lesion thickness has been developed by imaging the skin structure using microscope, X-Ray and ultrasound. However, the researches are not adapting the tactile inspection. In this research, an objective method to measure skin lesion thickness and determine the range of lesion thickness for each severity level on the standard Psoriasis Area and Severity Index (PASI) assessment tool by adapting the dermatologists’ tactile inspection is developed. The method obtains the 3D surface profile of skin lesion by using a 3D fringe projection scanner. The thickness of skin lesion is determined by averaging the elevations of lesion’s surface from an estimated lesion base (the assumed skin surface without the lesion).